MODERN COMPUTATIONAL APPROACHES TO POWERTRAIN MECHANICAL LOSS SOLUTION (Perner's Contacts, 2010)
The paper deals with modern powertrain development, mainly from the area of mechanical loss solution. The Virtual engine as a computational model is used for the solution. There are presented solutions of friction losses of a piston assembly, slide bearings or valvetrain contact couples. Mixed lubrication models are also presented. Hydrodynamic parts of solutions come from the Reynolds equation solution. A boundary lubrication model includes influences of surface roughness on contact pressure. Mechanical loss results for main powertrain parts are presented for the diesel in-line four-cylinder engine. The chosen computational results are validated by measurements